Modifiable social and structural factors influence COVID-19 vaccine intention among frontline workers in the Midwestern USA: a community-engaged survey study - Carolina Gonzalez Bravo; Sienna E Schaeffer; Aloha D Wilks; Martha L Carvour; Precious-Junia de-Winton Cummings; Kimberly C Dukes; Christopher D Ahlers; Fernando E Casado Castillo; Andrea Courtney; Alaina N Elliott-Wherry; Jessica E Knobbe; Natalie M Pineiro-Falcon; et al. (BMJ Public Health)
Introduction COVID-19 vaccines have been a crucial measure in the pandemic response, yet vaccine uptake has been variable across the population. We sought to identify social and structural factors associated with COVID-19 vaccine intention among adults in the Midwestern USA who worked in one or more frontline industries during the COVID-19 pandemic.Methods A community-engaged, cross-sectional online survey study was conducted between May and July 2022 among 889 workers. Guided by Thomas and Penchasky’s 5As theory of access and Thomson et al’s 5As taxonomy of vaccine uptake, we assessed modifiable social and structural factors related to access (transportation and convenient locations), affordability (time and incentives), activation (reminders), acceptability (experiences in a healthcare setting, political confidence and vaccine confidence) and accommodation (language inclusion and flexible appointments). Multinomial logistic regression was used to identify potentially modifiable factors that may influence vaccine intention among more than 200 surveyed workers who had not yet been vaccinated.Results Workers who intended not to receive the vaccine were at least three times more likely to report transportation challenges, limited time off work and inflexible vaccine appointments compared with those who intended to vaccinate. Interest in financial incentives was strongly endorsed among workers who did not intend to vaccinate and among those who were undecided. Concerns about vaccine safety or side effects did not influence intention, whereas concerns about vaccine effectiveness were more common among workers who did not intend to vaccinate. Mistrust in government leaders was associated with positive vaccine intention.Conclusions Vaccine intention among frontline workers is strongly influenced by social and structural factors and not solely by hesitancy about the vaccine itself.